Model Structure of Islamic Guidance and Counseling in the Healing Process of Inpatients - Riyadi, Agus; Wigati, Yunika Indah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
Studies on spiritual guidance services for patients in hospitals have been widely discussed. The result of those studies shows that hospital care must be holistic-comprehensive following WHO standards, which include bio-psycho-socio-spiritual. One of the four components is that the spiritual aspect is non-negotiable because it can support treatment and motivate the patient to heal. This study aims to answer (1) how the medical and spiritual needs of inpatients go to the healing process, (2) how to structure Islamic guidance and counseling models for inpatient healing in hospitals. This study is a qualitative field research. The data were collected through several techniques; observation, interview, and documentation. The results show that the medical and spiritual needs of patients at the hospital become one of the most important factors in the healing process. Therefore, suggested services to inpatients provided by hospitals are not only medical aspects but also psychological supports, as well as social and spiritual aspects. This four-aspect approach is called holistic-comprehensive healing. Thus, it is suggested that the structure of Islamic guidance and counseling models in hospitals are 1) al-Hikmah model, 2) al Mauizhoh al Hasanah model, and 3) Good mujadalah